2018
DOI: 10.21608/ejfsat.2019.6713.1040
|View full text |Cite
|
Sign up to set email alerts
|

AMELIORATIVE EFFECT OF POMEGRANATE MOLASSES ON DELTAMETHRIN INDUCED NEUROTOXICITY IN ADULT ALBINO RATS: BIOCHEMICAL, HISTOPATHOLOGICAL & IMMUNOHISTOCHEMICAL STUDY

Abstract: Background: Deltamethrin (DLM) is class II synthetic pyrethroid used worldwide as pesticides in agriculture, household pest control, protection of foodstuff, and disease vector control. Exposures occur mainly from the household application, contaminated food or water. Although initially thought to be least toxic, a number of recent studies revealed its toxic effects in different animal species. Aim: The current study aimed to evaluate oxidative stress effect due to DLM exposure on brain tissues of adult albino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…Although it is primarily produced in the liver, kidney, and erythrocytes, CAT has been detected in almost all organs. Our findings are consistent with the findings of many other researchers who found that the CAT activity was decreased when rats were treated with 6 mg/kg bw deltamethrin for seven days [84], dimethoate [85], diazinon [86], chlorpyrifos, methyl parathion, and malathion alone or in combination [87]. GPx transforms glutathione (GSH) to its oxidized form (GSSG), H 2 O 2 to H 2 O, and lipid hydroperoxides (ROOH) to the stable alcohols.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although it is primarily produced in the liver, kidney, and erythrocytes, CAT has been detected in almost all organs. Our findings are consistent with the findings of many other researchers who found that the CAT activity was decreased when rats were treated with 6 mg/kg bw deltamethrin for seven days [84], dimethoate [85], diazinon [86], chlorpyrifos, methyl parathion, and malathion alone or in combination [87]. GPx transforms glutathione (GSH) to its oxidized form (GSSG), H 2 O 2 to H 2 O, and lipid hydroperoxides (ROOH) to the stable alcohols.…”
Section: Discussionsupporting
confidence: 92%
“…Also, mice intoxicated with 30 mg/kg b.w./day of thiamethoxam for 28 days showed increase in the oxidative stress parameters such as MDA level in association with decrease in total antioxidants level [15]. A study of rats treated with 6 mg/kg bw deltamethrin for seven days [84] observed a significant increase in serum MDA. Several reports recorded increased MDA hepatic levels in fipronil and dimethoate treated rats [85,88].…”
Section: Discussionmentioning
confidence: 97%